Analisis Finansial Usahatani Nilam di Kecamatan Pasaman Kabupaten Pasaman Barat - Yozi Putri Sakinah; Muhammad Farrasky Delas Putra (Manajemen Kreatif Jurnal, 2025)
Patchouli oil is a potential Indonesian essential oil that is widely traded in the world market. This study aims to analyze patchouli farming financially using the B/C Ratio, Net Present Value, Internal Rate of Return and Payback Period at an interest rate of 9% in patchouli farming in Pasaman District. The method used in this study is a survey. The data analysis used in this study is quantitative descriptive, aimed at determining the financial feasibility of patchouli farming using investment criteria in the form of B/C Ratio, Net Present Value, Internal Rate of Return and Payback Period. From the investment criteria study, it was found that patchouli farming is feasible to be implemented, with a B/C Ratio value of 1.09. The NPV value is IDR 16,524,016.00, -. The IRR value is 97.00%. The Payback Period value is 5 years 10 months 7 days.